Specific characteristics of physical fitness at work anaerobic endurance type of rowers in canoe - Penchen Guo; A.U. Diachenko (H.S. Skovoroda Kharkov National Pedagogical University, 2014)
Purpose: to determine the effect of the reactive properties cardiorespiratory system to a special performance by canoe paddlers who specialize in the 200 m. Material : The study involved 22 paddler aged 18 - 29 years. Results : there were significant indicators of the reaction due to pulmonary performance and efficiency of anaerobic metabolism. The range of correlation coefficients (r) was -0.54 - 0.77 (T 50 V E) and 0,55-0,71 (V E). Conclusions : It was found that the optimization of the reactive properties of the cardiorespiratory system to realize the potential impact endurance rowers when using anaerobic nature. The greatest number of significant connections were indicators of efficiency and response of pulmonary ventilation. This allowed the evaluation of the functional improve information security work and increase specialized training sessions focus in the development of anaerobic endurance while working character in canoeing.